Synthesis, characterization and biological evaluation of a novel biscarboxymethyl-modified tetraphenylchlorin compound for photodynamic therapy. Issue 31 (10th March 2016) - Liao, Pingyong; Zhang, Xianghua; Zhang, Lijun; Wang, Xinrong; Zhu, Wei; Sun, Jingjian; Yan, Yijia; Zhang, Lixin; Chen, Na; Chen, Zhilong
Abstract : CompoundBCTC is an effective and a highly promising antitumor agent for photodynamic therapy. Abstract : A novel photosensitizer trans -2, 3-dihydro-2, 3-bis(carboxymethyl)-5, 10, 15, 20-tetraphenylchlorin (BCTC ) was synthesized. Its photophysical and photochemical properties, intracellular localization, photocytotoxicity in vitro and vivo were also investigated.BCTC displays a characteristic long wavelength absorption peak at 652 nm and shows a singlet oxygen quantum yield of 0.68 in DMF. Without light activation, BCTC was nontoxic to human esophageal cancer cells. However, upon light activation, BCTC exhibited significant photocytotoxicity. After PDT treatment, the growth of Eca-109 tumor in nude mice was significantly inhibited. This study suggests thatBCTC is an effective photosensitizer for PDT to tumors.